Codeswitching in Bilingual Children with Specific Language Impairment - Gutiérrez-Clellen, Vera F. (2009)
Children with specific language impairment (SLI) exhibit limited grammatical skills compared to their peers with typical language. These difficulties may be revealed when alternating their two languages (i.e., codeswitching) within sentences. Fifty-eight Spanish-English speaking children with and without SLI produced narratives using wordless picture books and conversational samples. The results indicated no significant differences in the proportion of utterances with codeswitching (CS) across age groups or contexts of elicitation. There were significant effects for language dominance, language of testing, and a significant dominance by language of testing interaction. The English-dominant children demonstrated more CS when tested in their nondominant language (Spanish) compared to the Spanish-dominant children tested in their weaker English. The children with SLI did not display more CS or more instances of atypical CS patterns compared to their typical peers. The findings indicate that children with SLI are capable of using grammatical CS, in spite of their language difficulties. In addition, the analyses suggest that CS is sensitive to sociolinguistic variables such as when the home language is not socially supported in the larger sociocultural context. In these cases, children may refrain from switching to the home language, even if that is their dominant language.